Impact of tumor location on clinical outcomes of gastric endoscopic submucosal dissection - Yoon, Ji Young (Baishideng Publishing Group Inc, 2014)
AIM: To determine whether there is a correlation between the location of the lesion and endoscopic submucosal dissection (ESD) outcome. METHODS: From January 2008 to December 2010, ESD of 1443 gastric tumors was performed. En bloc resection rate, complete resection rate, procedure time and complication rate were analyzed according to the tumor location. RESULTS: The rates of en bloc resection and complete resection were 91% (1318/1443) and 89% (1287/1443), respectively. The post-ESD bleeding rate was 4.3%, and perforation rate was 2.7%. Tumors located in the upper third of the stomach were associated with a longer procedure time and significantly higher rates of incomplete resection, piecemeal resection, and perforation than tumors below the upper third of the stomach. Posterior wall lesions had significantly longer procedure times and higher rates of incomplete resection and piecemeal resection than lesions in other locations. In multivariate analysis, posterior wall lesions and upper third lesions were significantly associated with incomplete resection and perforation, respectively. In post-ESD bleeding analysis, location was not a significant related factor. CONCLUSION: More advanced endoscopic techniques are required during ESD for lesions located in the upper third or posterior wall of the stomach to decrease complications and improve therapeutic outcomes.